Prevalence of congenital coronary artery anomalies as shown by multi-slice computed tomography coronary angiography: a single-centre study from Turkey. (December 2016) - Tongut, Aybala; Özyedek, Zeki; Çerezci, İsmail and Erentürk, Selim and Hatemi, Ali Can
Objective: Coronary artery anomaly (CAA) is a remarkable etiological factor for sudden cardiac death in young adults. The incidence of CAA is unknown, with most reliable data available based on postmortem/angiography investigations. This study aimed to assess the prevalence of different forms of coronary anomalies, and to investigate the relationships between demographic data and occurrence of CAA. Methods: A total of 2401 consecutive patients (1805 men; mean age, 56 ± 11.7 years), who were referred between January 2005 and December 2008 for noninvasive multi-slice computed tomography (MSCT) imaging, were retrospectively analysed. Results: A total of 225 cases (191 men; mean age, 55.9 ± 12) of CAAs were identified (9.37%). Because 11 patients had multiple muscular bridges of the coronary arteries, 236 coronary artery anomalies were found in these 225 patients. Cases were classified into three groups: group 1, coronary anomalies of origin and distribution (n = 36, 1.5%); group 2, anomalies of intrinsic coronary arterial anatomy (n = 180, 7.49%); and group 3, anomalies of coronary termination (n = 9, 0.4%). Conclusion: The prevalence of CAA was 9.37% in our single-centre study, which is consistent with previous research. A minimally invasive tool, such as MSCT angiography, should be used to identify CAA.